Pisanie automatyczne, czyli o trudnych związkach awangardy z nowoczesnością - Rakoczy, Marta (Zagadnienia Rodzajów Literackich, 2019)
The text refers to the surrealist invention of automatic writing examined in the anthropological and historical perspective. The aim of the article is to show the relationships of automatic writing with other non-literary cultural practices, especially graphological and spiritualistic. These practices explore the unconscious, strictly individual components of writing, aimed at revealing the social and psychological truth about the subject. They are also to show the domain of what is rejected by modern rationalism. In this article I want to show that the link between modernity, the avant-garde and the subconsciousness or superconsciousness is a complex epistemic fight with modern political and social administration that goes beyond the field of art to the field of broadly understood culture.